2017
DOI: 10.1590/s0100-736x2017001200015
|View full text |Cite
|
Sign up to set email alerts
|

Tutores de cães consideram a dieta caseira como adequada, mas alteram as fórmulas prescritas

Abstract: RESUMO: O estudo objetivou avaliar a adesão e a percepção dos proprietários de cães, residentes na cidade de São Paulo/SP, quanto ao emprego de dieta caseira no manejo nutricional de seu animal de estimação. Foram entrevistados por contato telefônico 55 proprietários que forneciam dieta caseira no manejo nutricional do seu cão. O questionário contemplou perguntas relacionadas ao preparo e eficiência das dietas, bem como o manejo dos animais. Verificou-se que considerável número (parcela) de prescrições (45,9%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
15

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 16 publications
0
15
0
15
Order By: Relevance
“…Another study 60 observed that 50.0% of owners that fed homemade diets to dogs or cats did not follow instructions precisely, only 15.2% of interviewed owners had a scale to weigh ingredients, and 28.3% of owners admitted to not using supplementation prescribed. A more recent study 9 observed that of the 110 owners that took part in the research, 60.0% made some kind of change in the prescribed diet, either changing type of meat or adding a different ingredient. Furthermore, 35.1% admitted not to follow properly the amounts of ingredients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study 60 observed that 50.0% of owners that fed homemade diets to dogs or cats did not follow instructions precisely, only 15.2% of interviewed owners had a scale to weigh ingredients, and 28.3% of owners admitted to not using supplementation prescribed. A more recent study 9 observed that of the 110 owners that took part in the research, 60.0% made some kind of change in the prescribed diet, either changing type of meat or adding a different ingredient. Furthermore, 35.1% admitted not to follow properly the amounts of ingredients.…”
Section: Discussionmentioning
confidence: 99%
“…The main reasons that may motive owners to change to a home-prepared diet are diseases that require dietary change, difficulty to interpret labels, concern about preservatives and better palatability 6,911 . But sometimes owners are not aware that homemade diets need complex preparation, specific ingredients, and supplements and may be more expensive than extruded pet food 12 .…”
Section: Introductionmentioning
confidence: 99%
“…A alimentação natural formulada depende da correta preparação e utilização por parte dos tutores, podendo contribuir negativamente para a saúde do animal quando mal preparada ou acondicionada. Mesmo em dietas prescritas por profissionais habilitados, os tutores podem sentirse à vontade para interferir na prescrição original, acrescentando ou retirando alimentos sem a orientação profissional (Halfen et al, 2017;Stockman et al, 2013).…”
Section: Resultsunclassified
“…Homemade diets are optimal in terms of palatability, which is key for the consumption of adequate amounts of food. However, owners may not comply with prescriptions (OLIVEIRA et al, 2014;JOHNSON et al, 2016;HALFEN et al, 2017); homemade diets are also questionable in terms of consistency, balance, and food safety (MICHEL, 2006).…”
Section: Types Of Dietmentioning
confidence: 99%